The use of lexical retrieval strategies by creative second language learners: A computational analysis of clustering and switching - Fernández-Fontecha, Almudena; Ryan, James (Studies in Second Language Learning and Teaching, 2023)
This study seeks to delve into the potential role of divergent thinking, a component of creativity, in second language learning. Specifically, we compare the use of lexical organization and production strategies of two groups of more and less creative EFL learners in year 12 through an automatic vectorial semantic analysis of their retrieval in three second language semantic fluency tasks. Consistent with previous research in the field of creativity, our findings indicate that the creative group retrieved more second language words than the less creative group. These words were less related to each other and to the stimulus categories than the words generated by the less creative group. While the creative participants’ retrieval was based on an extensive use of switching, a slight but non-significant trend was found in the production of longer clusters by the less creative participants. These results yield interesting insights into the potential role of creativity in second language learning.